Desenvolvimento dos servidores docentes da Universidade Federal do Pará: algumas reflexões - SOUSA, Sheila Gomes Carneiro (2020)
This work seeks to reflect on the training, capacity building and development of the teaching staff of the Federal University of Pará, with the Coordination of Training and Development (CAPACIT) in the main axis. It is characterized as a bibliographical and documentary review. From the readings it is possible to identify the theoretical conceptions about continuing teacher education. It presents the training, capacity building and development of the faculty of the Federal University of Pará, with the Coordination of Training and Development (CAPACIT) in the main axis.